Ruh Tanpa Tubuh, Tubuh Tanpa Ruh: Keterangan tentang Mati di Antara Universalisme Filsafati dan Partikularisme Antropologis - Muhammad Damm (Antropologi Indonesia, 2011)
Death can be understood merely as a transition from one life to the next or simply as an end of life. These two conceptions are established due to our lack in knowledge about what will happen to us after we die. In order to make any sense, both conceptions require an understanding of death (and also life) as individual matter, that the only death (and life) I experienced is always my own. Nevertheless, in the first conception death does not exterminate one’s self, while in the second conception death exterminate one’s self. However, nonexistence of any access to the first-person death experiences causes our understanding about death is always constructed from third-person point of view—in this case, live person’s point of view. As the result, we see that death also brings ontological transformation regarding to one’s corporeal body and identity. As endeavors to undertand what death is, there are tendencies to bring these conceptualizations of death to such philosophical universalism or anthropological particularism. This paper suggests that explanations about death must explain this event without strictly take one of these tendencies. Keywords: death, death as transition, death as denouement, transformation of corporeal body, transformation of personal identity